Simulating impairment through virtual reality. (September 2020) - McIntosh, Jacqueline; Marques, Bruno; Harkness, Robyn
Research on architectural technology for health care has rapidly increased in recent years; however, little research has been conducted on the use of virtual reality for simulating impairment. This exploratory research maps the experiences of people with impairments in the often-overlooked corridors and waiting rooms of an emergency department. It questions whether the experience of an impairment can be usefully simulated for empathetic design. While using participatory processes to develop a virtual reality simulation of waiting areas, this research applies three representative impairments and then surveys 30 architectural designers to find the emotional responses of the unimpaired to the design intervention. While this research is preliminary, it is particularly valuable for the comprehension of proposed designs during the early planning and design phases, without costly and time-consuming use of full participatory processes. It finds there is significant potential for the use of virtual reality as a technology to simulate the experiences of these spaces by individuals with impairment, enabling empathetic design, and offers direction for future research.